THE EFFECT OF MLC901 ON RED CELL DISTRIBUTION WIDTH (RDW) AS A PREDICTOR OF ACUTE ISCHEMIC STROKE OUTCOME IN ACUTE ISCHEMIC STROKE MODEL IN RATS - Ilham, Muhammad Arya Rifqi; Hunaifi, Ilsa; Dirja, Bayu Tirta (Folia Medica Indonesiana, 2025)
Stroke is the second leading cause of death globally, with ischemic stroke being the most prevalent type. Thrombolysis is the standard treatment for ischemic stroke; however, the rate of thrombolysis administration remains low. Therefore, neuroprotective therapies such as MLC901 are considered promising alternatives. The role of MLC901 in influencing red cell distribution width (RDW) during pathological ischemic stroke remains unclear. Hence, research on the effect of MLC901 on RDW is warranted. Male rats (n = 15) were divided into three groups: (1) acute ischemic stroke treated with MLC901 at a dose of 43.2 mg, (2) acute ischemic stroke treated with MLC901 at 21.6 mg, and (3) acute ischemic stroke treated with CMC-Na (positive control). Stroke was induced using the unilateral carotid artery occlusion (UCAO) method. RDW was measured before stroke induction and at 24 hours, 72 hours, and day 14. Neurological deficits were assessed using the foot fault score, and infarct volume was measured using ImageJ software. Following stroke induction, the positive control group had the highest mean RDW value, followed by the 21.6 mg and 43.2 mg MLC901 groups. However, there were no significant differences between the groups (p > 0.05). The positive control group exhibited greater neurological deficits compared to the MLC901 groups, with significant differences observed on days 7 and 14 (p < 0.05). Additionally, the positive control group had a significantly larger infarct volume than the MLC901 groups (p < 0.05). In conclusion, MLC901 did not affect RDW values but significantly reduced neurological deficits and infarct volume.